In the Wake of Marcial Valladares’ Folk Literature: his Collaboration with the Folklorists of the 19th Century - Fernández Salgado, Xosé A. (Madrygal. Revista de Estudios Gallegos, 2021)
The writer and linguist Marcial Valladares (1821-1903) was also the author of one of the first collections of Galician popular literature of the century XIX. In spite of not having given it to the prints at the time, it might be said that they had some degree of dissemination thanks to the fact that he himself used the coplas and sayings as a kind of linguistic authority to his well known Diccionario gallego-castellano (1884); in addition, Valladares was always generous with those scholars of the Spanish and Galician folklore that requested his collaboration providing them with his complete and varied handwritten collection. This article explores and analyses precisely Valladares’ contribution to the works and collections of Manuel Murguía, Antonio Machado y Álvarez, Juan A. Saco Arce, Francisco Rodríguez Marín, Casto Sampedro, Xosé Pérez Ballesteros, Antonio de la Iglesia and Alfredo Brañas. Besides, this examination goes to allow realize a historiographical trip through the most decisive folkloric investigations of the 19th century.